Prevalence and Influencing Factors of Test Anxiety Among Adolescent School Students in A South Indian Town – A Cross-Sectional Interventional Trial.: Life Sciences-Nursing - . V, Boominathan; S, Prabavathy (International Journal of Life Science and Pharma Research, 2023)
Test anxiety is a common issue among students. Some students find that anxiety interferes with their learning and testtaking to such an extent that their performance suffers. These students may study hard but perform poorly because they may have anxiety-provoking thoughts, such as a desire for perfection or a fear of failure. Furthermore, these negative thoughts may have other consequences, such as dissatisfaction with studies, which can lead to poor academic performance. This study aimed to determine the prevalence of test anxiety among adolescent students and to correlate the level of test anxiety among adolescent students with selected demographic variables. The research design was quantitative descriptive. Purposive sampling was used to select 144 adolescent students who fulfilled the inclusion criteria and were available during the data collection period at selected schools in Puducherry. They were divided into two groups to receive a writing intervention. The standardized Westside test anxiety scale was used to collect data. The majority of subjects (71 – i.e., 49.3%) had a high level of test anxiety. Among the others, 56 (38.8%) reported severe test anxiety. But only 17 (11.9%) had extremely high test anxiety. The test anxiety score was associated with selected demographic variables, with statistically significant associations in socio-demographic variables such as the mother's occupation and family monthly income. Test anxiety is one of the most common problems among students, and it is also regarded as one of the most significant barriers to academic success. Writing intervention was very effective in decresing tets anxiety. Therefore, interventions to reduce test anxiety among adolescents should be promoted to make the examination atmosphere more congenial.